Estimation of genetic distance using allele frequencies at microsatellite loci in buffalo populations - Vijh, R K; Mishra, Bina; Arora, Reena; Sharma, Uma; Tantia, M S (The Indian Journal of Animal Sciences, 2005)
The blood samples from 104 individuals were collected from unrelated animals belonging to 3 buffalo populations. The populations were Tarai, Bhadawari and Local populations of Kerala. The DNA was isolated and microsatellite data on 23 loci was generated. The data was subjected to analysis for the estimation of genetic distances based on arithmetic and geometrical considerations viz; Nei’s D, Allele sharing distance Das, Cavalli Sforza Edward’s Chord distance Dc, Prevosti distance Cp and Roger’s distance Dr. The phylogenetic treeltopology was prepared using both NJ and UPGMA method. The distances utilized for this purpose were population, as well as inter-individual distances. The genetic distance was least among Tarai and Bhadwari populations and were closely related and this may be attributed due to the fact that the two populations are in geographical contiguity. The bootstrap values on loci were 100% giving reliability to the tree.